An exploratory network analysis of mobile broadband provider's infrastructure relationships in Tamil Nadu, India - Sebastian Sigloch; Emanuele Giovannetti; Shailaja Fennell (International Telecommunications Society (ITS), 2016)
This study analyses the emergent network features of the upstream connectivity structure of three mobile broadband providers in the area included between the cities of Kancheepuram and Chennai in Tamil Nadu, India, from an original end-users perspective. This perspective is based on using a large dataset, collected by the authors, in February 2015, generated by the crowdsourcing-based Portolan Network Sensing Application on Android devices. The key feature of these data is that they are user generated and reflect mobility, as they were sourced from smartphones along the route between Chennai and Kancheepuram, rather than being based on stationary operators masts. Internet Service Providers traditionally rely on Border Gateway Protocols (BGP) for interconnecting purposes. Adding an end-user perspective to the existing BGP routing tables reveals a more complete picture of the underlying topology for the studied mobile broadband providers. The data were then used to conduct an Internet Periphery Analysis, pointing towards the roles of existing traffic peering agreements among the Internet Service Providers, and focussing on the role played by International Exchange Points (IXPs) key electronic infrastructures in the region. The analysis identifies the emergence of possible bottlenecks affecting upstream competition and the key role played by IXPs in providing a more widely distributed network access structure. This paper proposes to further study the usage of settlement free peering in fair competition and the preconditions of Quality of Service and service pricing in the Indian Mobile Broadband Market.
Keywords: 330; India; Tamil Nadu; Chennai; Mobile Broadband; Rural Broadband; ICT4D; Internet connectivity; Centrality; Networks; Complexity